Discovery of indole-derived pyridopyrazine-1, 6-dione γ-secretase modulators that target presenilin. Issue 4 (15th February 2015) - Pettersson, Martin; Johnson, Douglas S.; Humphrey, John M.; am Ende, Christopher W.; Evrard, Edelweiss; Efremov, Ivan; Kauffman, Gregory W.; Stepan, Antonia F.; Stiff, Cory M.; Xie, Longfei; Bales, Kelly R.; Hajos-Korcsok, Eva; et al.
Graphical abstract